2009
DOI: 10.1007/s00415-009-5065-y
|View full text |Cite
|
Sign up to set email alerts
|

The value of skin biopsy with recording of intraepidermal nerve fiber density and quantitative sensory testing in the assessment of small fiber involvement in patients with different causes of polyneuropathy

Abstract: The primary aim of our study was to demonstrate how the diagnostic characteristics of skin biopsy used to evaluate small fiber involvement in patients with different causes of polyneuropathy are intrinsically related to the method used to establish the reference values (cut-off values). We also investigated intraepidermal nerve fiber (IENF) density and abnormalities in quantitative sensory testing (QST) in patients with different causes of polyneuropathy and signs of small fiber involvement. A total of 210 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(47 citation statements)
references
References 37 publications
2
40
1
4
Order By: Relevance
“…For IENFD, data for patients with small fibre neuropathies vs healthy controls from Nebuchennykh et al [46] were used. This calculation revealed a minimum sample size of 16 was required per group for a power of >0.8 (power 0.816; difference in means 4.7; standard deviation 4.5; α = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…For IENFD, data for patients with small fibre neuropathies vs healthy controls from Nebuchennykh et al [46] were used. This calculation revealed a minimum sample size of 16 was required per group for a power of >0.8 (power 0.816; difference in means 4.7; standard deviation 4.5; α = 0.05).…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity (percentage of true positives) has ranged from 45% to 90% [7••, 32] and specificity (percentage of true negatives) from 95% to 97% [7••] using the lower fifth percentile as a cutoff. In one study, sensitivity was lower in patients with SFSN (35%) than in those with a mixed pattern of small and large fiber involvement (49%) [32]. The sensitivity for SFSN was even lower in symptomatic patients with a normal neurologic examination than in those who had clinical signs as well as symptoms [7••, 34].…”
Section: Nerve Fiber Analysis Of Skin Biopsiesmentioning
confidence: 98%
“…Using the fifth percentile as a cutoff, any ENFD equal or below this value indicates neuropathy. In different studies, the fifth percentile of the thigh has varied from 6.7 (unpublished observation) to 8 fibers/mm [31], and the fifth percentile of the calf has ranged from 5 to 6.7 fibers/ mm [31,32]. An early study of normative values for ENFD did not reveal any relation to age or gender, but a recent analysis of 188 healthy volunteers (97 women, 91 men) indicated that the mean ENFD gradually diminishes with increasing age [16].…”
Section: Nerve Fiber Analysis Of Skin Biopsiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diyabetik a¤r›l› distal simetrik nöropatinin ön planda ince sinir liflerini tuttu¤u iddias› çeflitli dönemlerde bu liflerin fonksiyonlar›n› ortaya koymay› amaçlayan yöntemlerin gelifltirilmesi çabalar›na yol açm›flt›r. Bu yöntemler aras›nda Kantitatif Duysal Test (KDT), otonom sinir sistemine yönelik testler ve epidermal sinir biyopsi yöntemleri say›labilir (20). Çift tepeli duysal yan›tlara iliflkin ilk hipotezler bu aç›dan umut verici görünmekle birlikte daha sonra yap›lan çal›flmalar çift tepeli yan›tlar›n kökenine iliflkin de¤iflik bilgiler sa¤lam›flt›r.…”
Section: Tart›flmaunclassified